2022
DOI: 10.3389/fphar.2021.730826
|View full text |Cite
|
Sign up to set email alerts
|

Application of Population Pharmacokinetic Analysis to Characterize CYP2C19 Mediated Metabolic Mechanism of Voriconazole and Support Dose Optimization

Abstract: Purpose: The aims of this study were to establish a joint population pharmacokinetic model for voriconazole and its N-oxide metabolite in immunocompromised patients, to determine the extent to which the CYP2C19 genetic polymorphisms influenced the pharmacokinetic parameters, and to evaluate and optimize the dosing regimens using a simulating approach.Methods: A population pharmacokinetic analysis was conducted using the Phoenix NLME software based on 427 plasma concentrations from 78 patients receiving multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…The clearance of VRC in children was approximately three times higher compared to adults [ 21 ]. A previous report indicated the clearance of VRC was 1.91 L/h in adult patients [ 22 ]. Our final PPK model demonstrated that the typical value of clearance was 7.35 L/h and the CYP2C19 genotype was the most important factor affecting VRC clearance.…”
Section: Discussionmentioning
confidence: 99%
“…The clearance of VRC in children was approximately three times higher compared to adults [ 21 ]. A previous report indicated the clearance of VRC was 1.91 L/h in adult patients [ 22 ]. Our final PPK model demonstrated that the typical value of clearance was 7.35 L/h and the CYP2C19 genotype was the most important factor affecting VRC clearance.…”
Section: Discussionmentioning
confidence: 99%
“…VCZ is extensively metabolized in the liver by enzymes of cytochrome P450 (CYP450), comprising CYP2C19, CYP3A, and CYP2C9 subfamilies [ 38 ], which may present genetic polymorphism and their expression is affected, resulting in a phenotype of poor, intermediate, or rapid metabolizers [ 172 ]. CYP2C19 enzymes convert VCZ into its inactive metabolite, VCZ-N-oxide [ 173 ].…”
Section: Voriconazolementioning
confidence: 99%
“…Individualized dose adjustment of VRZ may be necessary for different CYP2C19 genotypes. The proper dosage can be determined using TDM in conjunction with pharmacogenetic testing ( He et al, 2020 ; Li et al, 2021 ).…”
Section: The Impact Of Gene Polymorphisms On Vrzmentioning
confidence: 99%